Fishing and stock fluctuations / Taivo Laevastu - Laevastu, Taivo (1988)
The ever-changing fishery and our conception of it, diversity of objectives in fisheries and the search for stability; marine environment as determinant of fisheries, coastal or inshore environments and their fish ecosytems; availability of fish to gear, pelagic fish; effects of fishng and optimum take, production processes in fish ecosytems and the recruitment problem.